Nutrition literacy as a determinant for diet quality amongst young adolescents: A cross sectional study - Joulaei, Hassan; Keshani, Parisa; Kaveh, Mohammad Hossein (Progress in Nutrition, 2018)
The purpose of the present study was to assess the association between nutrition literacy and diet quality among young adolescents. In this cross-sectional study, 388 adolescents aged 13-15 were selected from secondary schools, Shiraz, Iran, using cluster random sampling method. The Revised Children’s Diet Quality Index (RCDQI) was assessed using a validated Food Frequency Questionnaire (FFQ) and nutrition literacy was measured via a 3-dimensional questionnaire. Ordinal regression was used to examine the association between nutrition literacy and the quartiles of RCDQI as well as its components. RCDQI mean and standard deviation and total nutrition literacy (T-NL) were 65.19 ± 8.96 and 52.98 ± 7.15 among all the participants. Diet quality scores were higher in boys. Sources that were mostly used to collect nutritional information included the Internet (18.6%), families (15.2%) and books (13.1%). Among boys, an increase in T-NL (OR: 1.049; CI 95% 1.001-1.098), interactive nutrition literacy (OR: 1.13; CI 95% 1.033-1.236), and critical nutrition literacy (OR: 1.086; CI 95% 1.016-1.161) could enhance diet quality. Furthermore, increase in functional nutrition literacy was associated with lower sugar intake and better energy balance in boys and higher dairy intake in girls. Since there was an association between health literacy and diet quality amongst adolescents, health policy-makers should develop new strategies with focus to increase understanding of nutrition literacy during adolescence years.